Logo-Autobiography and Its Effectiveness on Depressed Korean Immigrant Women. (January 2013) - Cho, Sunhee; Bernstein, Kunsook S.; Roh, Soonhee; Chen, Daniel C.
This study aimed to explore the effectiveness of logo-autobiography (LA) as a therapeutic modality for Korean immigrant women suffering from depression and perceiving their lives as meaningless. A nonrandomized quasi-experimental study was conducted with pretest, posttest, and a 4-week follow-up test. Forty subjects—20 with antidepressants and 20 without—were divided quarterly and assigned to the experimental group and the control group. The experimental group reported a significant lower score on depressive symptoms ( F = 6.832, p = .013; F = 19.800, p ≤ .001) and a higher score on meaning of life ( F = 12.294, p = .001; F = 12.232, p = .001) than did the control group immediately after completing the LA and a 4-week follow-up. The LA was more effective for the subjects in the nonmedication group than in the medication group. In conclusion, LA is effective in reducing depressive symptoms and increasing a sense of meaning in life among Korean immigrant women suffering from depression.